Neuroimaging predictors of treatment response in anxiety disorders. - Shin, Lisa M.; Davis, F Caroline.; VanElzakker, Michael B.; Dahlgren, Mary K.; Dubois, Stacey J. (2016)
Abstract: Although several psychological and pharmacological treatment options are available for anxiety disorders, not all patients respond well to each option. Furthermore, given the relatively long duration of adequate treatment trials, finding a good treatment fit can take many months or longer. Thus, both clinicians and patients would benefit from the identification of objective pre-treatment measures that predict which patients will best respond to a given treatment. Recent studies have begun to use biological measures to help predict symptomatic change after treatment in anxiety disorders. In this review, we summarize studies that have used structural and functional neuroimaging measures to predict treatment response in obsessive-compulsive disorder (OCD), posttraumatic stress disorder (PTSD), generalized anxiety disorder (GAD), and social anxiety disorder (SAD). We note the limitations of the current studies and offer suggestions for future research. Although the literature is currently small, we conclude that pre-treatment neuroimaging measures do appear to predict treatment response in anxiety disorders, and future research will be needed to determine the relative predictive power of neuroimaging measures as compared to clinical and demographic measures.; Keywords: Social anxiety disorder, Obsessive-compulsive disorder, Posttraumatic stress disorder, Generalized anxiety disorder, Amygdala, Medial prefrontal cortex, Anterior cingulate cortex, Orbitofrontal cortex, fMRI, PET.; Springer Open.